إنتاج حامض الستريك بوساطة هايفات الفطرAspergillus niger المنبتة حديثاً (University of Mosul-college of Basic Education, 2007)
درس إنتاج حامض الستريك من محلول السكروز بالطريقة المغمورة وبوساطة الفطر A. niger في مخمر سعة (5) لتر (بحجم عمل لترين ونصف) . ودرس حجم اللقاح بمدى (0.5-2.5%) وسرعة التحريك بمدى (1000)دورة بالدقيقة والتهوية (0.7-1.3) حجم/حجم ودرجة حرارة التخمر(25-40) درجة مئوية وفترة التخمر (24-188)ساعة، فتبين ان حجم لقاح (1%) وسرعة التحريك بمرحلتين 400 و 1000دورة في الدقيقة وكمية هواء (0.7) حجم/حجم بالدقيقة ودرجة حرارة (30) م○ وفترة تخمر (144) ساعة ، تعطي أعلى إنتاج من حامض الستريك حيث وصل الإنتاج الى (53) غم / لتر .Citric acid production by submerged fermentation with pellet growth of Aspergillus niger in stirred fermentor with five liter capacity and (2.5) liter working volume .Different cultural conditions such as inoculum volume with range (0.5-2.5%), air supply with range (0.7-1.3) v/v, agitation in one stage 1000 rpm and two stages (400) and (1000) rpm, incubation temperature with range (25-40 C0) , and time profile after inculcation with range of (24-188 hours) , and we found that inoculum volume (1%), air supply 0.7 v/v agitation with two satge 400 and 1000 rpm, incubation temperature,30C0, were optimized for enhance citric acid production. Maximum amount of citric acid obtained during this study was (53.0 g/l).